2017
DOI: 10.15842/kjcp.2017.36.4.008
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Daily Stress on Impaired Control through Emotion Dysregulation and Drinking Motives

Abstract: Alcohol use disorder (AUD) can be explained by some emotion-based hypotheses such as the self-medication hypothesis and negative reinforcement model. Accordingly, the aim of this study was to explore the dynamic relationships between daily stress, emotion dysregulation and drinking motives in the prediction of impaired control to drink alcohol in a clinical male sample. Male patients with AUD (n= 193) were recruited from alcohol centers of four psychiatric hospitals in South Korea. All participants completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
0
3
0
2
Order By: Relevance
“…Compared to control group, patients with AUD reported greater use of response modulation and attentional deployment but less of cognitive change [50]. Difficulties in emotion regulation in those with AUD may be consistent with a concept called 'misregulation' of substance use, which emphasises the importance of patients attempting to exercise control in ways that do not produce the desired outcome [61].…”
Section: Emotion Regulation Strategies In Populations Of Problem Drin...mentioning
confidence: 76%
See 3 more Smart Citations
“…Compared to control group, patients with AUD reported greater use of response modulation and attentional deployment but less of cognitive change [50]. Difficulties in emotion regulation in those with AUD may be consistent with a concept called 'misregulation' of substance use, which emphasises the importance of patients attempting to exercise control in ways that do not produce the desired outcome [61].…”
Section: Emotion Regulation Strategies In Populations Of Problem Drin...mentioning
confidence: 76%
“…It has been observed that momentary negative affect impairs the ability to discriminate negative emotions, whereas momentary positive affect facilitates the discrimination of positive emotions among individuals in early abstinence. The ability to differentiate emotions is thought to be a protective factor against relapse and alcohol-related problems [59,60], but emotion dysregulation may act as a relapse trigger even after a period of long-term sobriety [61]. Emotion and impulse management cji mogą działać jako wyzwalacz nawrotu nawet po okresie długotrwałej trzeźwości [61].…”
Section: Emotion Regulation and The Development Of Audmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, severity of substance use was not measured in many of the studies included in our review. It has been found that higher DERS scores are associated with greater alcohol dependence severity [ 13 , 86 , 87 ] and experiencing more motives to drink alcohol [ 88 ]. In other studies, heavy cannabis users had higher DERS scores than less frequent cannabis users [ 89 ], and polydrug users had higher DERS scores than those only diagnosed with AUD [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%